Simulated annealing for multiple construction project scheduling with multiple resource constraints - Seyed Mohsen Shahandashti. (2009)
Multi-project scheduling is one of the most important and challenging parts of project scheduling. Having multiple projects with activities competing for multiple limited resources is common for almost all construction companies. However, available models can not handle properly scheduling of real multiple projects. This research as its main contribution proposes a model for scheduling multiple projects with multiple resource constraints using Simulated Annealing algorithm. This model is more efficient than previously proposed ones since it is not as time consuming and impractical for real cases as exact methods and it is not as sensitive to the problem type as heuristics. This model can be used for a variety of real multi-project scheduling problems and it is easy to reproduce and follow by engineers.